Fish detection around offshore artificial structures: preliminary results from hydroacoustics and fishing surveys. (December 2015) - Punzo, E.; Malaspina, S.; Domenichetti, F.; Polidori, P.; Scarcella, G.; Fabi, G.
Summary: The spatial distribution of fish assemblages was investigated through either hydro‐acoustic surveys (using a Multibeam Echosounder) or fishing surveys (using trammel nets) carried out at increasing distance from two gas extraction structures in the Adriatic Sea and characterized by different building architecture: one, a four‐leg platform; the other a subsea well‐site. Both types of surveys were monthly and performed for 1 year starting after installation of the structures. Primary scope of the study was to evaluate whether the combination of the two methodologies could provide a more comprehensive insight into the fish communities associated with artificial structures. The findings showed that associating the Multibeam Echosounder survey with the fishing survey provided complementary information on the spatial distribution and abundance of fish in the water column surrounding the artificial structures. Both methodologies evidenced the presence of a greater abundance and biomass of fish close to the structures in respect to reference sites. In addition, fish abundance and biomass were generally greater in the surroundings of the four‐leg platform than at the well‐site, a possible consequence of the larger volume of the former.